LOCAL RECURRENCE AND 5-YEAR SURVIVAL AFTER CONSERVATIVE SURGERY IN STAGES I AND II IN PATIENTS WITH BREAST CANCER TREATED BY THE BRAZILIAN UNIFIED HEALTH SYSTEM FROM JANUARY 2011 TO DECEMBER 2019 AT PÉROLA BYINGTON HOSPITAL - Conceição, Karoline de Oliveira Senna; Sarro, Jonas SarroJonas; Cavagna, Felipe; Shida, Jorge; Gebrim, Luis Henrique (Mastology, 2021)
Introduction: Breast cancer is the most common neoplasm in women in Brazil and in most of the known countries, and for this reason, and early diagnosis and treatment is essential to provide the best possible survival. Conservative breast surgery has been used as a standard procedure for the local treatment of breast cancer in the early stages. As a consequence of the preservation of breast tissue, ipsilateral recurrence in some patients is predictable. An ipsiateral recurrence rate of 10.4% was observed over an average follow-up period of 67.5 months). The survival data of patients diagnosed with breast cancer are important to know our service and evaluate the treatments provided to patients with the objective of improving the patients ́ more and more their quality of life and of trying to achieve the best possible treatment. Objective: To identify data related to 5-year survival after conservative surgery in stages I and II in patients with breast cancer treated at Pérola Byington Hospital. Materials and Methods: Data were collected from medical records of patients with breast cancer classified in stages I and II at Pérola Byington Hospital. Results: 11,237 patients were diagnosed with breast can- cer at Perola Byington Hospital from January 2011 to December 2019, among which 9,477patients underwent surgery as part of their treatment. Among the patients who underwent surgery, 4,593 (48.5%) had conservative surgery and 4,884 had radical surgery (51.5%). Most conservative surgeries were performed using the quadrantectomy technique in a total of 43.14% (4,088) of all surgeries and about 89% of conservative surgeries. Other techniques used were adenectomy / ade- nomastectomy with 2.10% of all surgeries, segmental resection 0.33% and 1.30% segmentectomy. The 5-year survival of 11,327 patients diagnosed with breast cancer in general was around 75% and 89% among patients undergoing surgical treatment. Patients in clinical stage I who underwent conservative surgery had a survival rate of less than one year (0.27%), of one to two years (0.54%) of two to three years (0.61%), of three to four years (0.34%), of four to five years (0.61%) and of more than five years (97.6%). The surgeries performed that resulted in free margins for invasive neoplasia were 93.27%, and 2.53% required a reoperation to reach free margins. Conclusions:The data related to the survival of breast cancer patients submitted to conservative surgery collected at Pérola Byington Hospital were similar to the data found in Dutch women demonstrating a survival very close to 97% to 99%. In American women, the 7-year survival rate in initial cases (stage I) was 97.8%. Conservative surgery when combined with radiotherapy had results in relation to 5-year survival which are very close to the ones patients undergoing mastectomy had.